A Review on the Cords & Plies Reinforcement of Elastomeric Polymer Matrix - S. S., Mahmood; M. S., Mat Shayuti; Zulkafli, Hassan; Hazlina, Husin (IOP Science, 2016)
Steel, polyester, nylon and rayon are the main materials of cords & plies that have been reinforced in the natural rubber to produce quality tyres but there is few research reported on cord and plies reinforcement in silicone rubber. Taking the innovation of tyres as inspiration, this review's first objective is to compile the comprehensive studies about the cords & plies reinforcement in elastomeric polymer matrix. The second objective is to gather information about silicone rubber that has a high potential as a matrix phase for cords and plies reinforcement. All the tests and findings are gathered and compiled in sections namely processing preparation, curing, physical and mechanical properties, and adhesion between cords-polymer.